Recent advances in IB-group metal electrocatalysts for hydrogen conversion and utilization - Wen-Xuan Lv; Kai-Xuan Jiang; Yue-Bao Chen; Peng-Fei Yin; Hui Liu; Xi-Wen Du (Materials Today Catalysis, 2025)
The green production, conversion, and utilization of hydrogen energy rely heavily on key technologies such as water electrolysis and hydrogen fuel cells. As essential components of these technologies, metal catalysts play a crucial role in determining device efficiency and economic viability. Currently, most electrocatalysts still rely on noble metals; however, their high cost and resource scarcity severely limit large-scale application and commercialization. Therefore, the development of cost-effective and high-performance alternatives to noble metal catalysts has become a major research focus. IB-group metals (Cu, Ag) have emerged as promising candidates for electrocatalysis due to their low cost, high electrical conductivity, and excellent corrosion resistance. However, their d10 electronic configuration results in weak adsorption of catalytic intermediates, leading to inherently low catalytic activity. Over the past decade, advancements in synthesis techniques and atomic/electronic structure modulation strategies have enabled the transformation of IB-group metals, particularly Cu and Ag, into highly efficient electrocatalysts for the hydrogen evolution reaction (HER) and oxygen reduction reaction (ORR). This review systematically summarizes recent progress in the synthesis and structural optimization of IB-group metal catalysts, with a particular focus on their applications in water electrolysis and hydrogen fuel cells. By analyzing key factors such as crystal structure and electronic configuration, we elucidate the fundamental mechanisms influencing catalytic performance. Finally, we discuss future perspectives on IB-group metal catalysts in clean energy technologies, highlighting their potential to accelerate the development of hydrogen energy and contribute to global carbon neutrality goals.